Leading the revolution - Hamel, Gary (Harvard Business School Press, 2000)
This text examines the underlying principles behind the radical innovation of companies and individuals. It explores and identifies the key criteria for building companies that are activist friendly and draws on examples of business activists who revolutionized their own firms.